FAKTOR-FAKTOR POTENSIAL DALAM KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI EMPIRIS DI KANTOR PELAYANAN PAJAK PRATAMA PONDOK GEDE BEKASI BARAT) - Christina Erawaty Laswara; Munawaroh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of Service Quality, Understanding of Tax Regulations and Tax Sanctions as the potential factors in the Compliance of Individual Taxpayers. This study uses a quantitative approach. The subject of this study was KPP Pratama Pondok Gede, Bekasi Barat, while the object of research was the Individual Taxpayer. Source of data used primary data by observation and distributing questionnaires to taxpayers. The data analysis technique used descriptive statistical analysis and regression method. The results of this study showed that Understanding of Taxation Regulations partially have a significant effect on Individual Taxpayer Compliance, while the Quality of Service and Tax Sanction did not have a significant effect partially on Individual Taxpayer Compliance, Service Quality, Understanding of Tax Regulations, and Tax Sanctions have simultaneously affects on the Compliance of Individual Taxpayer.